Feeding strategies to obtain high quality milk in intensive dairy sheep production systems - Frutos P.; Toral P.G.; Lavín M.P.; Hervás G.; Mantecón A.R. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
Castile and Leon is the main producing region of ovine milk in Spain, with more than 60% of national milk production and more than 40% of sheep census. Current systems of dairy sheep production in this area are characterized by an important increase in milk yield (55%) in the last decade and a lower number of farms. These changes result from enlarged flock size, use of specialized breeds, intensification, and a high individual production (over 300 L/ewe on average), which rely on feeding systems including no grazing and low forage: concentrate ratios. Under this situation, the nutritional value of the milk fat, in terms of impact on consumers’ health, can be detrimentally affected. It is known that moving away from pasture-based diets increases undesirable saturated and decreases potentially health-promoting (e.g., 18:3n-3, CLA, or trans-11 18:1) fatty acid (FA) levels. On the other hand, it provides an incomparable scenario to develop nutritional strategies to enhance milk quality. Dairy ewe diet supplementation with vegetable or marine lipids enables modulation of milk FA composition towards a healthier profile. However, the latter strategy causes milk fat depression, which prevents its application under practical farm conditions. Other compounds, such as tannins, may also modulate milk FA composition. From a research point of view, it is expected that new disciplines (e.g., nutrigenomics), may provide new insights into the mechanisms underlying the nutritional regulation of mammary lipogenesis and enable to modify, naturally and effectively, ovine milk fat without impairing animal performance.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)